Association between thyroglobulin polymorphisms and autoimmune thyroid disease: a systematic review and meta-analysis of case–control studies - Zhang, Ming-Liang; Zhang, Dong-ming; Wang, Cai-E.; Chen, Xiao-Long; Liu, Fang-Zhou; Yang, Jian-Xue (Genes and immunity, 2019)
Emerging evidence revealed that thyroglobulin (TG) contributes to the development of autoimmune disease, and the relationship between TG and autoimmune thyroid disease (AITD) is still controversial. The aim of this study was to quantify the association between rs2076740 , rs853326 , rs180223 , and rs2069550 TG polymorphisms and risk of AITD using a meta-analysis approach. We identified all studies that assessed the association between TG polymorphisms and AITD from PubMed, Embase, and Web of Science databases. A total of 3013 cases and 1812 controls from ten case–control studies were included. There was no significant associations found between rs2069550 , rs180223 , and rs853326 polymorphisms and AITD risk. The association between the rs2076740 polymorphism and AITD risk was significant in the codominant model ( P = 0.005), suggesting the CC rs2076740 genotype might be a protective factor for AITD. Sensitivity analysis by removing one or two study changed the results in dominant rs2076740 and rs853326 and rs2069550 allele models ( P = 0.016, 0.024, 0.027). Latitude and ethnicity significantly affected the association between rs2076740 and rs2069550 polymorphisms and AITD, indicating their protective effects in allele or dominant model ( P = 0.012, 0.012, 0.012, 0.009, 0.009). The association between rs2076740, rs2069550 , and rs853326 polymorphisms and AITD risk is significantly affected by study characteristics.